2010
DOI: 10.1016/j.joca.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical distribution of synovitis in knee osteoarthritis and its association with joint effusion assessed on non-enhanced and contrast-enhanced MRI

Abstract: Definite synovitis was present in the majority of knees with or without effusion with the commonest sites being posterior to the PCL and in the suprapatellar recess. Joint effusion as measured on PD fs images does not only represent effusion but also synovial thickening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
141
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 26 publications
5
141
1
4
Order By: Relevance
“…Hawker et al reported that working hours were also a possible risk factor for nocturnal knee symptoms (4). Conversely, it is documented that knee OA patients have synovitis even in the early stages of the disease, and its prevalence and number of regions increase with the severity of OA (31). More regions with synovitis in severe knee OA may be related to an increasing prevalence of nocturnal knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…Hawker et al reported that working hours were also a possible risk factor for nocturnal knee symptoms (4). Conversely, it is documented that knee OA patients have synovitis even in the early stages of the disease, and its prevalence and number of regions increase with the severity of OA (31). More regions with synovitis in severe knee OA may be related to an increasing prevalence of nocturnal knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…It is documented that knee OA patients have synovitis even in the early stages of the disease and its prevalence and number of regions increase with the severity of OA. 9 More regions with synovitis may be related to an increasing prevalence of nocturnal pain. 4 Previous studies have shown that BT is effective on pain in OA.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial enhancement by the contrast agent provides superior image quality for the assessment of synovial volume and differentiates synovitis from joint effusion by increased vascular perfusion and capillary permeability of the synovium [167]. Synovitis scores obtained by contrast-enhanced MRI showed good correlation with arthroscopic and microscopic synovitis scores [168].…”
Section: Mri In Osteoarthritismentioning
confidence: 93%
“…Interventional studies assessing intraarticular corticosteroids or NSAIDs and paracetamol demonstrated associations between decreased synovitis and reduction of pain in patients with knee OA [171,172]. Several semiquantitative and quantitative contrast-enhanced MRI assessment systems using different subregional approaches have been proposed to quantify synovitis [65,167,[173][174][175].…”
Section: Mri In Osteoarthritismentioning
confidence: 99%